Burden of psychological symptoms and disorders among individuals with hepatitis B: a systematic review, meta-analysis and meta-regression - Low, Chen Ee; Ge, Genevieve; Yeong, Trevor James Jun-Ming; Rana, Sounak; Loke, Sean; Kow, Wei Chieh; Lee, Ainsley Ryan Yan Bin; Ho, Cyrus Su Hui (Frontiers in Psychiatry, 2025)
IntroductionHepatitis B is a highly contagious viral infection that has long been a significant global health concern. Given its adverse effects on the course of the disease, evaluating psychiatric outcomes is important. Despite indications of an increased risk of psychological outcomes among those with hepatitis B, the extent of this association remains unclear.MethodsThis PRISMA-adherent systematic review (PROSPERO: CRD42024564246) searched PubMed, Embase, Cochrane, and PsycINFO for all studies evaluating the prevalence and risk of anxiety and depressive symptoms in individuals with hepatitis B. Random effects meta-analyses and meta-regression were used for primary analysis.ResultsA total of 31 studies were included. We identified a high prevalence of depressive symptoms (Proportion=19%, 95% CI: 11-31) and anxiety (Proportion=30%, 95% CI: 18-45) among individuals with hepatitis B. There was also a significantly increased risk of depressive symptoms (RR=1.45, 95% CI: 1.00-2.09, P=0.049) and anxiety (RR=1.40, 95% CI: 1.11-1.78) in individuals with hepatitis B compared to controls. Subgroup analyses indicated that older age and chronic hepatitis B infection were associated with a higher prevalence of anxiety and depressive symptoms. The systematic review found that being single, unemployed, having a lower income, a lower education level, high comorbidities, and a family history of mental illness were significant risk factors for poorer psychological outcomes.ConclusionOur study highlights an increased vulnerability to anxiety and depressive symptoms among individuals with hepatitis B. We emphasize the urgent need for early detection and additional support for this at-risk group.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024564246.